Survei Manajemen Olahraga Petanque pada UKM Petanque Unnes Kota Semarang Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study was to understand the Sports Management of Petanque Student Activity Unit in Semarang State University in 2020. This study used qualitative research with a descriptive approach. The results of the study are seen from the indicators: 1) Planning is already running in accordance with the management function. 2) Organizing is carried out by dividing the duties of each member according to the existing organizational structure in UKM.3) The management and coach have arranged the movement in implementing the training program by making a schedule and training program according to the needs of the athlete. 4) Supervision of management is carried out on coaches, athletes and also funding in UKM. The conclusion of this research is the management of UKM Petanque Unnes has constraints from the number of trainers who only have 1 person, the recruitment system that is not attractive, and also the maintenance of facilities and infrastructure that is not optimal. The suggestion that the researcher gave was that the research nest gave, that the management should add a coach so that there is a backup coach who is ready to replace, the athlete recruitment system is also made attractive to introduce and introduce this new sport. Facilities and infrastructure should be checked and maintained regularly to avoid damage.